The Meningkatkan Keseimbangan Statis Melalui Permainan Tradisional Egrang Siswa Sekolah Dasar Kelas V - Nurhasanah, Siti Hajar; Mashud, Mashud; Warni, Herita (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Objective. The study aimed to determine the appropriate learning method to improve students' static balance. Materials and Methods. This study used the Kemmis model of PTK method with phases: preparation, implementation, observation, and reflection. Data collection instruments with static balance measurement standing stork test. The target population in this study were all fifth grade students of SD Negeri 3 Batu Tungku, Panyipatan District, the target population was the fifth grade of SD Negeri 3 Batu Tungku, totalling 7 people consisting of 2 men and 5 women. In this study will use consists of data analysis techniques with static balance norms and then proceed with the percentage formula. Results. Based on the results of data analysis, it can be seen that there is an increase in learning outcomes through two cycles according to the research data. Data analysis of first cycle completeness was 14.28% and second cycle completeness was 71.57%. Conclusion. The results of research analysis based on data show that traditional Egrang games can be used by educators in choosing learning methods used to improve the ability of static balance skills of students, especially at the Dasa School level.